Satluj river flow variations since AD 1660 based on tree-ring network of Himalayan cedar from western Himalaya, India. (12th June 2015) - Misra, Krishna G.; Yadav, Ram R.; Misra, Sandhya
Abstract: Water availability is one of the main concerns for future developmental and economic activities in semi-arid to arid western Himalaya. However, the water supply potential of Himalayan rivers, essential for residents living along rivers, is not well understood in long-term perspective largely due to the scarcity of observational data. To fill this void, we developed Satluj river flow reconstruction for October to current year June (OJ) extending back to AD 1660. We used a network of ring-width chronologies of Himalayan cedar ( Cedrus deodara ) from seven moisture stressed, homogeneous sites in Kinnaur, Himachal Pradesh. In this pursuit, a total of 302 increment cores from 212 trees of Himalayan cedar from the Satluj river basin in Kinnaur, Himachal Pradesh were used. The reconstruction capturing 40% of the variance in calibration period (1923–1952) revealed that Satluj river flow, consistent with the decreasing trend in winter precipitation, decreased since the 1990s. The reconstruction spanning over the past 345 years showed 10-year, 20-year high, and low flow records in the 20th century.